Porphyrin adsorption and ligand exchange at the (110)-TiO2 / organic liquid interface - Götz, Klaus; Stollberg, Isabella; Prihoda, Annemarie; Bertram, Florian; Metwalli, Ezzeldin; Zech, Tobias; Unruh, Tobias (Surface Science, 2022)
Highly efficient dye-sensitized solar cells (DSSCs) have been prepared on the basis of porphyrin dyes with significant success. Recent studies have demonstrated a correlation between the solar cell efficiency and the configuration of the adsorbed porphyrin molecules at the surface of the semiconducting support material. The preparation of dense self assembled monolayers (SAMs) of upright standing porphyrin molecules on TiO2 surfaces was achieved from toluene solutions only when using a molecular exchange reaction. Here, an exchange study of an oleic acid (OLA) SAM on a <110> TiO2 surface by porphyrin molecules is presented. The exchange reaction has been studied by ex-situ as well as in-situ X-ray reflectometry (XRR) measurements. It was found that an almost complete exchange of OLA with porphyrins can be achieved. With increasing coating times the orientation of the porphyrin molecules relative to the substrate surface changed from flat lying to upright standing.
CRIS-Team Scopus Importer:2022-04-15
Keywords: DESY; functionalization; interface; porphyrin; rutile; X-ray reflectometry